Soft Probes for Bio-electrochemical Imaging - Lin, Tzu-En (Springer Theses, Recognizing Outstanding Ph.D. Research, 2019)
This book discusses the development of various reliable scanning electrochemical microscopy (SECM) imaging techniques for studying the distribution of biomarkers and nanomaterials in thin and thick animal samples, plant antioxidant (AO) defense systems, as well as human melanoma. The authors demonstrate that SECM could improve the diagnosis and understanding of different melanoma stages on the basis of highly resolved maps of the tyrosinase distribution. Tyrosinase is the key enzyme involved in fruit maturation and is a biomarker for melanoma. As such the book presents various tyrosinase SECM detection strategies developed for the analysis of the spatial distribution of tyrosinase in melanoma and in banana samples. It describes the first imaging of the redox active proteins within the entire mouse heart with an SECM system using a spider probe composed of eight independent microelectrodes. Further, it investigates distributions of injected graphene nanoribbons (GONRs) for drug deliveryby Soft-Probe-SECM. Lastly, the book outlines a non-invasive electrochemical strategy for mapping the AO activity of apple peel using Soft-Probe-SECM.